COMUNIDAD DE AVES COMO SISTEMA COMPLEJO ADAPTATIVO: PATRONES ESPACIO-TEMPORALES EN UN AGROECOSISTEMA DE LOS ANDES PERUANOS - Salvador Rodriguez, Julio (2024)
The interpretation of biological communities as complex adaptive systems aims to demonstrate their ecological patterns at different scales and their environmental relationships. In this survey, we analyzed species diversity and alternative stable states patterns of the bird community in an Andean agroecosystem located on the central-western slope of the Peruvian Andes (Cajatambo District, Lima - Peru), on a temporal and spatio-temporal scale. We evaluated their bird community through 24 line transects, located in seven plant formations along two ecoregions, between 2 700 and 4 600 masl, during the dry and rainy seasons of 2015 and 2016. The temporal patterns did not show differences in species diversity between seasons. We determined the existence of a single temporary alternative stable states; however, we evidenced changes in their species composition between dry and rainy seasons, suggesting a greater functional redundancy in dry season than rainy season due to temporal variability of small granivore-insectivore species. Regarding the spatio-temporal patterns, the plant formations of Polylepis forests, some scrubs and agricultural lands presented high values of species diversity. In addition, we determined eight alternative stable states in relation to one or more plant formations and seasonality. Finally, a higher proportion of regime changes was found in the community alternative stable states located in the Meso-Andean ecoregion as opposed to the Puna-Humid ecoregion, which would suggest that this bird community has a greater self- organization and adaptability in the face of environmental stochasticity.